Impact of Spoilage Bacterial Populations on Discoloration of Beef Steaks - Colton L. Smith; Ifigenia Geornaras; Mahesh N. Nair (Meat and Muscle Biology, 2024)
There is limited understanding of the relationship between the growth of spoilage microflora and fresh meat color. Therefore, the objective of this study was to investigate the impact of the growth of common spoilage bacteria on the color stability of color-stable (longissimus lumborum; LL) and color-labile (psoas major; PM) beef muscles. Beef striploins (LL) and tenderloins (PM) (USDA Choice, n = 8) were wet aged (14 d), after which they were decontami- nated and fabricated into 1.27-cm thick steaks. Steaks were randomly assigned as decontaminated (DCON) or inoculated (INOC). The surface of INOC steaks was inoculated (ca. 4 log CFU/cm 2 ) with a mixture of spoilage bacteria, while an equivalent volume of phosphate-buffered saline was applied to the surface of DCON steaks. Steaks were aerobically retail displayed for up to 9 d. Each day, objective and subjective color evaluation and microbiological analyses were conducted. Aerobic plate counts on INOC steaks were 8.9 (LL) and 9.3 (PM) log CFU/cm 2 at the end of retail display. Corresponding counts on DCON steaks were < 2.7 (LL) and < 3.4 (PM) log CFU/cm2. For LL steaks, there was a treatment × display day interaction (P < 0.05) for lightness (L* ), redness (a*), yellowness (b*), lean color scores, surface discoloration, and bac- terial levels. On days 6 – 8, redness was lower (P < 0.05) for INOC compared to DCON LL steaks, while lean color scores and surface discoloration were lower (P < 0.05) for DCON compared to INOC LL steaks. For PM, there was a treatment × display day interaction (P < 0.05) for a* values, surface discoloration, and bacterial levels. Surface discoloration was greater (P < 0.05) for INOC steaks compared with DCON steaks on days 4 and 5. The results indicate a connection between surface discoloration and microbial growth on beef LL and PM steaks, and differences in bacterial growth kinetics could explain some of the differential color stabilities between these muscles.